Equitable Power Domination Number of Various structure in Molecular Geometry - R. Revathi; S. Banupriya; P. Vignesh (Utilitas Mathematica, 2025)
The power dominating set ???? ⊆ ???? in ???? = (V, E) is said to be equitable power dominating set when each vertex ???? ∈ ???? − ???? has observed nearby vertex ???? ∈ ???? such that difference between degree of ???? and the degree of ???? is less than or equal to 1, i.e. |???? (u ) − ???? (???? )| ≤ 1. The equitable power domination number of a graph ???? is the minimal cardinality of its equitable power dominating set, and it is represented by the notation ???????????????? (????). Molecular geometry is the three-dimensional arrangement of the atoms that comprise a molecule. In this research, we examine fair equitable power domination number of various structure in Molecular geometry.